Inside Cover: A Dinuclear Ruthenium‐Based Water Oxidation Catalyst: Use of Non‐Innocent Ligand Frameworks for Promoting Multi‐Electron Reactions (Chem. Eur. J. 28/2015). Issue 28 (6th July 2015) - Laine, Tanja M.; Kärkäs, Markus D.; Liao, Rong‐Zhen; Siegbahn, Per E. M.; Åkermark, Björn
<x xml:space="preserve">Abstract</x> The development of catalysts for the oxidation of water using ligands with a non‐innocent character could potentially be employed for the rational design of efficient water‐oxidation catalysts. In their Full Paper on page 10039 ff., B. Åkermark, M. D. Kärkäs, R.‐Z. Liao and co‐workers explore the mechanistic details associated with a dinuclear Ru‐based water‐oxidation catalyst. Combining experimental studies and quantum chemical calculations provides insight into the fundamental principles controlling the reactivity of the catalyst, in which metal–ligand cooperation is a vital part.